Imagination and Reality: The Construction of National and Personal Identity in Synge's The Playboy of the Western World - Hussein, Median Mashkoor (Al-Adab Journal, 2021)
This paper investigates how John Millington Synge uses the theme of imagination in his play The Playboy of the Western World to introduce a critical view of the construction of personal and national identities of those people, Irish people. It argues that the play juxtaposes two contradicted images of the construction of personal and national identities. On the one hand, the play satirizes the way that the villagers use their imagination to create their own hero to help them revive their primitive national identity. On the other hand, it emphasizes the importance of imagination in creating personal identity. The play questions the authenticity of the notion of national identity by depicting it as a human-made phenomenon, but at the same time it makes use of it by showing how imagination helps to change human life.